Branding Islamic Educational Institutions Through Promotion Strategy at MI Tarbiyatul Akhlaq Taman - Jaya Roza Azzukhrufi (Chalim Journal of Teaching and Learning, 2025)
This study aims to analyze the promotional strategy in building the brand of an Islamic educational institution at MI Tarbiyatul Akhlaq. Using a qualitative approach with a case study design, the research was conducted from March to May 2025. The main subjects were the head of the madrasah, teachers, staff, and community leaders. Data was collected through observation, semi-structured interviews, and document analysis. The results show that the madrasah’s promotional strategy is holistic, combining print media (brochures, banners) and digital media (WhatsApp, Instagram). The madrasah’s brand is strengthened through daily spiritual activities of students, such as Dhuha prayer and reading Asmaul Husna, which serve as unique selling points. This finding highlight that the limitations of internal resources are overcome by utilizing the social legitimacy of community leaders, which increases credibility in the public’s eyes. Thus, this study concludes that Islamic education branding can be effectively built through simple, creative, value-based, and community-supported promotional strategies, providing an important contribution to the study of community-based madrasah branding.